Extraction and characterization of nanocellulose from bemban fibre for cement-based composite - Cut Rahmawati; Muhammad Faisal; Roslidar; Fitriani; Jawad Ahmad; Intan Muliana (Case Studies in Construction Materials)
The utilization of natural fibers in composite cement faces issues due to the presence of lignin and hemicellulose, which hinder the strength of the fibers as reinforcements. This study aims to investigate the characteristics of Bemban Fibres (Donax canniformis)/BF as reinforcement in cement-based composite. Cellulose was extracted from the stem fibres using alkali treatment, bleaching, and acid hydrolysis methods to obtain Bemban Fibre Nanocellulose (BFNC) which exhibits favorable compressive strength properties. Microstructural characterization was conducted through X-ray Diffraction Analysis (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Thermogravimetric Analysis (TGA). Compressive strength testing was performed on cement-based composites with the addition of BFNC at 0 %, 1 %, 2 %, and 3 % by weight. The results indicated that BFNC contains 42.4 % cellulose. The diameter of the BFNC ranged from 6 to 28 nm. BFNC exhibited significant potential in terms of thermal properties compared to untreated fibers. As a highly effective reinforcing component, it demonstrates excellent resistance to degradation at elevated temperatures and improves the mechanical strength of the cement-based composite. The incorporation of 1 % BFNC was found to improve the compressive strength by 9.38 % compared to the control specimens. This indicates that BFNC processed through acid hydrolysis has a better surface and enhanced bonding capabilities between particles. The utilization of 1 % BFNC has been proven effective in increasing the compressive strength of cement composites, making it suitable as a reinforcing material and feasible for application in construction.